Serum Zinc and Vitamin A Levels in Tuberculosis Patients: A Comprehensive Study - Bhadarge, Gangaram; Bankar, Nandkishor; Singh, Sudhir (Pharmaceutical Science: New Insights and Developments Vol. 4, 2025)
Introduction: Malnutrition is a major public health problem in all developing countries. Tuberculosis, an infectious disease caused by the bacteria Mycobacterium tuberculosis (MTB), is also a major cause of death in humans around the world. According to a World Health Organization (WHO) survey, MTB infects one-third of the world's population, with 9.6 million new tuberculosis (TB) infections and 1.5 million deaths confirmed in 2021. The progression of tuberculosis is highly dependent on the hosts' immunological status, and it requires the availability of micronutrients such as iron, zinc, and vitamins A and D to function properly. Aim: The study of serum zinc levels and vitamin A levels in tuberculosis patients. Materials and Methods: This study included 40 newly diagnosed PTB patients of both sexes with the age group of 18-60. The time period of this study was from September 2020 to April 2021 a non-randomized controlled trail was involved. Vitamin A was Estimated by the Colorimetric Method. EDTA samples were used for the Hemoglobin, ES and WBC count was estimated on 3 parts coulter counters. Albumins were estimated on AU480 Analyzer. Results: There was a strong correlation between serum zinc and vitamin A levels P < 0.01) Hb, P < 0.01) and serum albumin levels P < 0.01) were also strongly correlated with the vitamin A levels; however, WBC P < 0.01) and ESR P < 0.01) were negatively correlated with the vitamin A levels. Considering the significant role of Zn, its support may be effective in resolving the disease. Until treatment, intermediate levels of serum Zn in people with pulmonary TB were very low. The serum Zn level with the highest decrease in stage 3, which was statistically significant, was a steady decline in the number of people researching lung TB. Conclusion: In view of the above, the patient's nutritional status may be the most important determinant of infection tolerance. Zinc deficiency can have an indirect impact on Vitamin A metabolism by reducing the levels of circulating protein. Because of this, the addition of zinc in combination with vitamin A may be helpful in achieving the disease status.